Implementasi Pembelajaran Al-Qur’an dengan Metode Ummi di Sekolah Menengah Pertama Islam Terpadu (SMP IT) Darussalam Sangatta Kutai Timur. - Munawaroh, Siti (SYAMIL: Jurnal Pendidikan Agama Islam (Journal of Islamic Education), 2016)
The background of this research is SMPIT DaarussalaamSangatta East Kutai as the only one education institute ofjunior high schools in East Kutai that implement Ummi Method and Al – Qur’an study as the priority program. The aim of this research is to acknowledge the background of Ummi method at the institution, the implement of Al – Qur’an study using Ummi method and to discover thesupport and obstacle factors. The type of research is field research, the resource of data is from interview, observation and documentation. The result of this research is the implement of Qur’an Study using Ummi method runs well. It is shown 48 students  running of Khataman  and Imtiihan Al – Qur’an year 2015 collaborate with Ummi Foundation Centre Surabaya. The support factors for Al – Qur’an Study using Ummi method is the achievement of Ummi method study system and parenting support. Meanwhile the obstacle factors faced in Al – Quran study at SMPIT Daarussalaam is the teacher standardization and the incomplete facilities. According to the discovery, writer suggests to the school to increase the teachers’ quality by providing intensive training and regular evaluation.